Predictors of reading and writing achievement in first graders - Bazán Ramírez, Aldo (2000)
The achievement of reading and writing ta ks of different complexity leve! was evaluated. Twohundred eighty-eight first-grade children responded to 76 items cla sified on the basis of one mor phological and one functional criterion. Variables regarding teaching practices as well a children's characteristics were used a predictors of reading and writing ta ks. A multiple regression analysis suggested that teacher's judgment  concerning the child's reading-writing  acquisition, sorne visual or auditive deficits, and final average on Spanish course explained almost 40% of the dependen! variable variance.  Result are discussed in terms of their teaching-leaming implications.